PENINGKATAN PENGETAHUAN BISNIS BAGI PELAKU UMKM KECAMATAN GENTENG KOTA SURABAYA - Iswara, Ulfah Setia; Suwitho, Suwitho; Palupi, Dian; Setyabudi, Teguh Gunawan (ABDI MAKARTI, 2024)
Genteng District, as an icon of the city of Surabaya, has a lot of economic potential for the community, especially in the culinary and handucraft sectors, which must continue to be explored to achieve optimal economic growth. Efforts to improve the community's economy are carried out by focusing on creative economic businesses that continue to develop. The aim of this service program is to provide digital marketing training and assistance in business ethics and bookkeeping which aims to support business development. Business partners, namely MSMEs in Genteng District who operate in the culinary and handicraft sectors, continue to innovate in marketing products digitally. MSME participants have generally been involved in their business for a long time, but some have not kept financial records. This activity was carried out through partner survey stages, digital marketing training and mentoring, business ethics and bookkeeping for MSMEs in Genteng District, and evaluation of digital marketing implementation to expand sales coverage and business continuity amidst the challenges of increasingly competitive competition. MSME players are aware of the importance of online marketing applications, business ethics and business financial records.